Late Quaternary vegetation dynamics from central parts of the Madeira River in Brazil - Feitosa, Yuri Oliveira; Absy, Maria Lucia; Latrubesse, Edgardo Manuel [UNESP]; Stevaux, José Candido [UNESP] (Soc Botanica Brasil, 2015)
The present study reconstructs the paleovegetation of a varzea (seasonally flooded) forest in the central parts of the Madeira River floodplain in Brazil using palynological data. Forty-nine cut-bank sediment samples from the Madeira River were processed in the study; from these, ten samples contained pollen: two contained pollen from the Middle Pleniglacial age, one contained pollen from the Tardiglacial age, six contained pollen from the Holocene, and one contained more recently deposited pollen. The Middle Pleniglacial pollen belonged to a primary succession varzea forest, while the Tardiglacial pollen represented a late succession varzea forest. On the other hand, the three Holocene samples showed the characteristic composition of chavascal (water-logged forest) or lacustrine varzea forest, and three samples belonged to a late succession varzea forest. The most recent pollen deposit represented a secondary succession varzea forest. This paleovegetation showed a typical mosaic distribution, which may be explained by the fluvial dynamics, high species richness and diversity in the varzea forest, and the presence of dominant species.
Keywords: Cut-bank sediment; Late Pleistocene-Holocene; Palynology; Southern Amazonian tributary; Varzea